2023
DOI: 10.1002/admt.202201871
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale Hybrid Fabrication: Volumetric Printing Meets Two‐Photon Ablation

Abstract: perfusable channels. In the past decades, microfluidic technology has mostly relied on photolithography and soft lithography applied to materials like glass and elastomers (i.e., PDMS), and has been largely limited to 2D devices. [3,6] In recent years, 3D printing has emerged as a powerful tool to generate highly complex, freeform structures with enhanced functionalities, leading to great advances in various fields from photonic crystals to tissue scaffolds. [7][8][9][10][11][12] While two-photon stereolithogr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 57 publications
0
24
0
Order By: Relevance
“…1 Without the ability to embed immediately addressable and perfusable vasculature, these engineered human tissues do not remain viable over the time required to provide therapeutic benefit. [2–7] Recent advances in extrusion [8–10] , embedded [3,11–14] , and light-based [1517] bioprinting have begun to address this critical need. Yet no method currently allows the free-form patterning of hierarchical, branching vasculature composed of smooth muscle cell-laden shells that surrounds endothelialized lumens in acellular or densely cellular tissue matrices.…”
Section: Introductionmentioning
confidence: 99%
“…1 Without the ability to embed immediately addressable and perfusable vasculature, these engineered human tissues do not remain viable over the time required to provide therapeutic benefit. [2–7] Recent advances in extrusion [8–10] , embedded [3,11–14] , and light-based [1517] bioprinting have begun to address this critical need. Yet no method currently allows the free-form patterning of hierarchical, branching vasculature composed of smooth muscle cell-laden shells that surrounds endothelialized lumens in acellular or densely cellular tissue matrices.…”
Section: Introductionmentioning
confidence: 99%
“…This approach overcomes important limitations of traditional AM methods, where layer‐by‐layer addition of material hinders production rates, part quality, and geometric flexibility. More broadly, VAM is capable of rapid production of complex parts in a broad range of polymeric materials (e.g., high viscosity acrylates, [ 1 ] thiol‐enes, [ 4,5 ] cell‐laden hydrogels, [ 6,7 ] preceramic, [ 8 ] and glass‐forming [ 9 ] polymer resins).…”
Section: Introductionmentioning
confidence: 99%
“…Rizzo et al, demonstrated the feasibility of combining the high-speed printing of large VBP constructs with perfusable macrochannels with the subsequent 2-photon ablation of high-resolution (∼2 mm) microchannels. [614] The resulting convoluted and multi-scale tubular networks greatly resemble native vascular structures, but given the short working depth of the 2-photon ablation process (∼500 mm), such a converged approach will be challenging to upscale. In its current form, such an approach can only be used to pattern thin constructs of the border regions of larger VBP-produced structures.…”
Section: Advanced Bioprinting Strategies For Mimicking Na-tive Tissue...mentioning
confidence: 99%
“…In studies demonstrating this approach, the 3D resolution of grafted structures is significantly enhanced, given the design freedom in across all planes that is possible in this approach. However, as with several multi-photon approaches, the working depth of this approach is rather limited (< 1 mm for various studies employing hydrogels) [614,615,643] and approximately 2-3 mm for microscopy applications. [644,645] This means that convoluted 3D printed structures of clinically relevant sizes could not be biofunctionalized with full spatial freedom.…”
Section: Enhancing Cell Fate Regulation Through the Development Of Sm...mentioning
confidence: 99%
See 1 more Smart Citation